The Effect of Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Loan to Deposit Ratio, and Cost to Income Ratio on the Firm Value of Banks Listed on the Indonesia Stock Exchange for the 2021–2024 Period - ATHAYYA, Awen Alif; YULAZRI, Yulazri (PT Keberlanjutan Strategis Indonesia, 2025)
This research investigates the influence of financial performance ratios on firm value within the banking industry listed on the Indonesia Stock Exchange (IDX). Firm value is assessed using the Tobin's Q metric, with the independent variables comprising the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Net Interest Margin (NIM), Loan-to-Deposit Ratio (LDR), and Cost-to-Income Ratio (CIR). A quantitative causal method employing multiple linear regression analysis is applied. The data were obtained from the financial reports of conventional banks registered on the IDX. Out of 45 banks considered as the study population, 41 met the sample criteria over the 2021–2024 period, resulting in 123 observations. Prior to regression, classical assumption tests were performed to validate the model. The findings reveal that CAR exerts a negative and significant impact on firm value, while NPL, NIM, and LDR show negative and significant relationships. Conversely, CIR demonstrates no significant influence. These outcomes imply that factors such as capital strength, asset quality, and credit distribution efficiency are key determinants shaping investors' evaluation of banking firm value.